2018
DOI: 10.1074/jbc.m117.808733
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Gβγ subunits of Gi protein coupled with S1P receptor on multivesicular endosomes in F-actin formation and cargo sorting into exosomes

Abstract: Exosomes play a critical role in cell-to-cell communication by delivering cargo molecules to recipient cells. However, the mechanism underlying the generation of the exosomal multivesicular endosome (MVE) is one of the mysteries in the field of endosome research. Although sphingolipid metabolites such as ceramide and sphingosine 1-phosphate (S1P) are known to play important roles in MVE formation and maturation, the detailed molecular mechanisms are still unclear. Here, we show that Rho family GTPases, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 32 publications
1
51
0
2
Order By: Relevance
“…These results are entirely consistent with the data from the cellular model. Recent research on newly identified roles of the G βγ subunits has shown that the G βγ subunit of S1PR can function in the maturation of MVEs for exosomal cargo sorting via the regulation of the actin cytoskeleton through Rho family small GTPase (22). Therefore, we evaluated the changes in the actin cytoskeleton after apoptotic stimuli.…”
Section: Aevs Are Released From Various Cells At Various Modes Of Apomentioning
confidence: 99%
“…These results are entirely consistent with the data from the cellular model. Recent research on newly identified roles of the G βγ subunits has shown that the G βγ subunit of S1PR can function in the maturation of MVEs for exosomal cargo sorting via the regulation of the actin cytoskeleton through Rho family small GTPase (22). Therefore, we evaluated the changes in the actin cytoskeleton after apoptotic stimuli.…”
Section: Aevs Are Released From Various Cells At Various Modes Of Apomentioning
confidence: 99%
“…Secretion of sphingosine-1-phosphate (S1P), a ceramide derivative, is instrumental in promoting angiogenesis during tumor growth (Mizugishi et al, 2005; Nagahashi et al, 2012; Ogretmen, 2018; Pyne, El Buri, Adams, & Pyne, 2017; Spiegel & Kolesnick, 2002; Spiegel & Milstien, 2003; Takabe, Paugh, Milstien, & Spiegel, 2008; Takabe & Spiegel, 2014). It was found that stable complexes of S1P with G-protein coupled receptors (GPCRs) are critical for formation of exosomes in MVEs through constitutive activation of Rho GTPases and stabilization of F-actin (Kajimoto et al, 2018). However, it has not been determined if these stable complexes are formed on exosomes that could then function as extracellular signalosomes.…”
Section: Exosomes In Cancer: Target Tissue Biohacking and Hijacking Omentioning
confidence: 99%
“…Research into the exosomal sorting of the related S1P 1 receptor has revealed a mechanism for how GPCRs are sorted away from degradative MVBs and into MVBs that contain exosomes. Continuous stimulation of the S1P 1 receptor following internalization activates Rac1 and Cdc42 on MVBs, a process that requires the Gβγ subunits of the heterotrimeric G i protein. Inhibition of Rho GTPase activity or the inhibition of Gβγ prevents the release of S1P 1 in exosomes, suggesting that actin polymerization and GPCR signaling near the limiting membrane of MVBs is critical for exosome release.…”
Section: Alternative Destinations For Gpcrs—autophagy Exosome Packagmentioning
confidence: 99%
“…Continuous stimulation of the S1P 1 receptor following internalization activates Rac1 and Cdc42 on MVBs, a process that requires the Gβγ subunits of the heterotrimeric G i protein. Inhibition of Rho GTPase activity or the inhibition of Gβγ prevents the release of S1P 1 in exosomes, suggesting that actin polymerization and GPCR signaling near the limiting membrane of MVBs is critical for exosome release. These findings have highlighted the importance of GPCRs in exosomal signaling, and provide critical mechanistic insight into how GPCRs are sorted into exosomes.…”
Section: Alternative Destinations For Gpcrs—autophagy Exosome Packagmentioning
confidence: 99%